Penetapan Kadar Fenolat Total dan Uji Aktivitas Antioksidan Ekstrak Kulit Segar Buah Manggis (Garcinia Mangostana Linn.) - Zulharmita, Zulharmita; Prajuwita, Mia; Boestari, Agusri (Jurnal Sains dan Teknologi Farmasi, 2010)
The determination of totally phenolic compounds in methanol extracted of cortex fruit of Garcinia manggostana Linn has been done by Folin-Ciocalteau method. The antioxidant activity has been performed using 1,1-diphenyl-2-picrihydrazil (DPPH) as reagent, that measured spectrometrically compared with gallic acid as antioxidant standard compound. The total phenolate compounds found in fresh peel of mangosteen was 1,64Â±0.18% w/w which calculated as gallic acid equivalence and the antioxidant activity with a value of IC50 was 251,12 Î¼g.